2002
DOI: 10.2460/javma.2002.221.52
|View full text |Cite
|
Sign up to set email alerts
|

Small Animals/Avian

Abstract: Diagnostic value of a fecal panel in dogs with diarrhea appears to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…This study confirms, for the first time intra vitam, that intestinal mucosal hemorrhagic necrosis is the principal histologic lesion found in dogs with HGE. In contrast to previous histologic studies,5, 6 some infiltration of neutrophilic granulocytes in the intestinal mucosa was observed; however, in relation to the severe epithelial destruction, the influx of inflammatory cells was disproportionally minor. Acute mucosal destruction, in general, could be explained by ischemia,22 hyperthermia,23 acute parvoviral infection,24 and enterotoxins 25, 26, 27, 28.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This study confirms, for the first time intra vitam, that intestinal mucosal hemorrhagic necrosis is the principal histologic lesion found in dogs with HGE. In contrast to previous histologic studies,5, 6 some infiltration of neutrophilic granulocytes in the intestinal mucosa was observed; however, in relation to the severe epithelial destruction, the influx of inflammatory cells was disproportionally minor. Acute mucosal destruction, in general, could be explained by ischemia,22 hyperthermia,23 acute parvoviral infection,24 and enterotoxins 25, 26, 27, 28.…”
Section: Discussioncontrasting
confidence: 99%
“…Some reports have mentioned that lesions in dogs with HGE mainly affect the small intestine,5, 9 whereas other reports have stated that these lesions are particularly severe in the colon 8. In the present patient population, we demonstrated that the entire intestinal tract was affected in dogs with HGE and that mucosal damage is generally more severe in the large intestine.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations